The Relationship Between Knowledge Of Young Women And The Benefits Of Sp8 Point Acupressure To Reduce Dysmenorrhea Pain In Sigulang Village, Padangsidimpuan Tenggara District, 2022 - Dewi Aminasty Siregar; Rahmah Juliani Siregar; Elvi Suryani; Maryam Latifah Harahap (Jurnal EduHealth, 2023)
Dysmenorrhea pain causes 50% of all women in the world to suffer. In 2008, there were around 54.89% cases of primary dysmenorrhea in Indonesia. Meanwhile, the rest are sufferers in the secondary category. This pain makes women unable and unable to carry out activities and activities so that it can reduce the individual's quality of life. Dysmenorrhea is caused by the production of prostaglandin F2 alpha originating from endometrial cells in excessive amounts. One way that can be done to treat dysmenorrhea is with acupressure. This research was conducted in Sigulang Village, Padangsidempuan Tenggara District, with the aim of increasing knowledge and insight towards school-age adolescent girls. In order to reduce dysmenorrhea or menstrual pain non-pharmacologically by massaging using acupressure techniques. This research uses the Pre Experimental Design method in the research process. Counseling on acupressure techniques and assistance were carried out during this research process. After being given training and knowledge about dysmenorrhoea, young women can understand the benefits of acupressure massage to reduce menstrual pain or dysmenorrhoea. There was an increase in knowledge with a score of 81.81% of teenagers with good knowledge and 18.18% in the sufficient category.